2005
DOI: 10.1002/mus.20378
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional topography of the motor endplates of the rat gastrocnemius muscle

Abstract: Spatial distribution of motor endplates affects the shape of the electrical activity recorded from muscle. In order to provide information for realistic models of action potential propagation within muscles, we assembled three-dimensional maps of the motor endplates of the rat medial gastrocnemius (MGM) and lateral gastrocnemius (MGL) muscles. The maps were assembled from histological cross sections stained for acetylcholinesterase activity. Within MGL, the motor endplates formed three columns along its longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…MG and LG muscles consist of multiple compartments with multiple motor endplates [18], [19]. Bipolar intramuscular wire electrodes were inserted near motor endplates located in the distal region of MG and the proximal region of LG.…”
Section: Methodsmentioning
confidence: 99%
“…MG and LG muscles consist of multiple compartments with multiple motor endplates [18], [19]. Bipolar intramuscular wire electrodes were inserted near motor endplates located in the distal region of MG and the proximal region of LG.…”
Section: Methodsmentioning
confidence: 99%
“…A reference electrode was inserted underneath the skin, in the region above the gluteus maximus muscle. Given the distribution of fiber type in SO and LG muscle regions (Armstrong and Phelps, 1984) and muscle architecture (Prodanov et al, 2005), the EMG pick-up area consisted of slow oxidative fibers in the SO and a majority of fast glycolytic fibers in the LG. Electrode placement was verified by stimulation through the implanted wires.…”
Section: Sensors Implantationmentioning
confidence: 99%
“…However, SO muscle and its epimuscular myofascial connections were not affected. MG and LG muscles consist of multiple compartments with multiple motor endplates (De Ruiter et al, 1995;Prodanov et al, 2005). To excite these muscles, bipolar intramuscular wire electrodes were inserted near the motor endplates located in the distal region of MG and the proximal region of LG.…”
Section: Surgerymentioning
confidence: 99%
“…In addition, the electrodes were placed rather superficially within MG and LG muscle bellies, and submaximal stimulation was applied to make sure that only MG and LG muscle fibers were excited. As only one compartment of each MG and LG muscle was stimulated (De Ruiter et al, 1995;Prodanov et al, 2005), not all muscle fibers of these muscles were excited. A pilot experiment, in which excitation of LG and MG via nerve stimulation was compared with that via intramuscular stimulation, showed that approximately 20% of maximum active ankle moment exerted by MG and LG muscles fibers was exerted when stimulating intramuscularly (Tijs et al, 2014).…”
Section: Experimental Protocolmentioning
confidence: 99%